Retreatment of chronic hepatitis C patients who failed previous therapy with directly acting antivirals: A multicenter study. (July 2020) - El Kassas, Mohamed; Alboraie, Mohamed; El Badry, Mohamed; Youssef, Naglaa; Omar, Heba; El Sheemy, Reem Y.; Al Balakosy, Amira; Ashraf Ahmed Mohamed, Ossama; Gamal Naguib Meleak, Gina; Dabbous, Hany; Hassan Ahmed Fouad, Mohamed; Wifi, Mohamed-Naguib; et al.
Highlights: Virological non responders to sofosbuvir based anti HCV therapy are considered as difficult to treat population. Retreatment of prior non reponders with another DAAs was safe and effective. SVR 12 rate among previously non responders was 97.12%. Abstract: Aim of the study: The current study aimed to evaluate the efficacy of different DAAs regimens in the treatment of chronic hepatitis C (CHC) Egyptian patients who failed to achieve SVR after their treatment with SOF-based regimens. Methods: This was a retrospective observational multicenter study that included CHC patients that failed to achieve cure on SOF-based regimens who were re-treated using different DAAs regimen and were allocated according to national guidelines for the treatment of hepatitis C. Primary outcome was to assess the SVR12 rate among prior non-responders after retreatment with a second course of DAAs. Results: Our study included 172 patients who failed to achieve SVR after treatment with SOF-based treatment regimen [age: 51.2 ± 11.3, 58.7% men]. Included patients were retreated using SOF/DCV/RBV, SOF/ r/PAR /OMB /RBV, SOF/DCV/SIM, SOF/LDV ± RBV or SIM/SOF. SVR12 was successfully attained in 95.35% (164/172) of the included non-responders. Conclusion: The current multicenter study proved the efficacy of various DAAs regimens issued by the National Committee for Control of Viral Hepatitis for retreatment of relapsed CHC Egyptian patients.